Penguatan Pendidikan Karakter Berbasis Literasi pada Murid Sekolah Dasar - Syamsuriyanti Syamsuriyanti; Sulis Sri Padipa (Jurnal Ilmu Pendidikan Dasar Indonesia, 2023)
This study aims to analyze strengthening literacy-based character education in primary school students. A qualitative research method was used with a descriptive approach at Romang Polong State Primary School, Gowa Regency. Data were collected through observation, interviews, and documentation, then validated through data triangulation. The results showed that the role of teachers in strengthening character education is reflected through programs such as Scouting and religious brotherhood, as well as literacy cultures such as reading corners, reading parks, and libraries. The application of student character includes human values, discipline, perseverance, and spirituality. Literacy shapes the surface by introducing ethical concepts, developing critical skills, empathy, effective communication, and self-identity. The integration of character education and literacy is expected to form quality students with positive values who can contribute to a better society.